COMPARISON OF MARS AND BINARY LOGISTIC REGRESSION MODELS FOR IDENTIFYING STUNTING RISK FACTORS IN TODDLERS IN TELUK WARU, EAST SERAM REGENCY - Johan Bruiyf Bension; Ferry Kondo Lembang; Nurul Fadillah Idris; Norisca Lewaherilla (PATTIMURA UNIVERSITY, 2026)
In 2022, the prevalence of chronic stunting in Indonesia reached 21.6%, surpassing the World Health Organization (WHO) threshold of 20%. East Seram Regency reported an even higher prevalence of 24.1%, with Teluk Waru District identified as one of the areas most affected due to low compliance with healthy lifestyle practices. This study aimed to compare the performance of Multivariate Adaptive Regression Splines (MARS) and Binary Logistic Regression in analyzing risk factors for toddler stunting in Teluk Waru District, East Seram Regency. Data were collected through direct anthropometric measurements at the Integrated Health Post (Posyandu) of Teluk Waru Health Center with 60 respondents. The findings revealed that Binary Logistic Regression outperformed MARS, achieving R2 = 72.7% accuracy in predicting stunting. Significant determinants of toddler stunting included a history of illness, provision of supplementary food for pregnant women, and iron tablet consumption during pregnancy. The novelty of this study lies in the application of a comparative modeling approach—MARS versus Binary Logistic Regression—in identifying stunting risk factors at a district level with high prevalence. Practically, the results can assist local health authorities in prioritizing maternal nutrition and disease prevention programs to reduce stunting.